Analisis Pembuatan Susu Kedelai dengan Gula Kulit Singkong (SKGKS) Terhadap Kadar Nutrisi dan Uji AKtivitas Anti Bakteri Coliform - Nur Latifah, Rais (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2021)
Milk is one of the nutrients needed by the body. Milk can come from animal milk or vegetable milk. Soybean has a protein content equivalent to cow's milk which is about 3.5 g/100 g with a lower fat composition of 2.5 g/100 g. The sugar in the manufacture of vegetable milk is made from cassava peel waste. This research uses an enzymatic method that is able to hydrolyze starch in cassava peel. The resulting sugar is applied in the manufacture of low-fat soy milk that can be consumed by children to adults. The production of soy vegetable milk in this study was divided into two types of milk samples. The manufacture of soy milk begins with processing soybeans into soy juice. There are two types of soy milk in this study, type I is soy milk with a composition ratio between soybeans and water of 1:10, namely SKGKS I. While type II soy milk is soy milk with a composition ratio between soybeans and water of 1:35, namely SKGKS II. Both types of milk were analyzed for nutritional content and tested for anti-bacterial activity. The results showed that SKGKS 2 had a higher nutritional value than SKGKS 1. The nutritional content of SKGKS 2 was 11.56 g carbohydrates/mL milk and 2.93% milk protein. SKGKS II has a lower fat content than SKGKS 1, which is 1.23 g of fat/mL of milk. SKGKS types I and II showed a pH range of 6.74-7.12 with a storage time of 9 days. SKGKS II has a higher fiber content of 18.56 g with a food fiber content of 12.34 g. The results of the bacterial test showed that the two milk samples did not exceed the microbial contamination and were in accordance with the requirements of the Indonesian National Standard (SNI) No. 06.8-7388-2009.